2021
DOI: 10.1042/bsr20210280
|View full text |Cite
|
Sign up to set email alerts
|

Low NLRP3 expression predicts a better prognosis of colorectal cancer

Abstract: Background: NOD-like receptor pyrin domain-3 (NLRP3) inflammasome activation is a double-edged sword in tumorigenesis. Whether NLRP3 is involved in the progression and prognosis of colorectal cancer (CRC) remains elucidated and is the focus of this study. Methods: Immunohistochemistry (IHC) was applied on tissue microarray to determine the expression of NLRP3 in CRC patients. All 100 patients were divided into the low NLRP3 group and the high NLRP3 group according to their NLRP3 IHC scoring. Additionally, CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…In line with this, activation of NLRP3 by high glucose levels was demonstrated by Wang et al [138]. Shi and colleagues [139] recently showed significantly upregulated expression of NLRP3 in colon adenocarcinoma tissues as compared to adjacent normal tissue. In addition, high expression of NLRP3 was associated with poor prognosis and reduced survival of colon cancer patients [139].…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 53%
See 1 more Smart Citation
“…In line with this, activation of NLRP3 by high glucose levels was demonstrated by Wang et al [138]. Shi and colleagues [139] recently showed significantly upregulated expression of NLRP3 in colon adenocarcinoma tissues as compared to adjacent normal tissue. In addition, high expression of NLRP3 was associated with poor prognosis and reduced survival of colon cancer patients [139].…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 53%
“…Shi and colleagues [139] recently showed significantly upregulated expression of NLRP3 in colon adenocarcinoma tissues as compared to adjacent normal tissue. In addition, high expression of NLRP3 was associated with poor prognosis and reduced survival of colon cancer patients [139]. The main role of inflammasomes is the regulation of caspase-1 activity, which promotes the secretion of pro-inflammatory cytokines IL-1β and IL-18.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Inflammasome dysregulation has been most often associated with tumor prognosis, although there have been some controversial results reported. While some authors have shown a clear association between high levels of inflammasome activity and poor survival, for example in colorectal cancer and laryngeal squamous cell carcinoma [ 14 , 134 ], others have proposed NLRP3 inflammasome-dependent pyroptosis induction as a therapy for cases of acute myeloid leukemia or colorectal cancer [ 135 ].…”
Section: Epigenetic Targeting Of the Nlrp3 Inflammasomementioning
confidence: 99%
“…The NLRP3-inflammasome is initially generated to restore cellular homeostasis and to avoid infections or situations in which damage may occur. Nevertheless, exacerbated NLRP3 inflammasome activation is involved in the pathogenesis of many diseases such as Alzheimer’s, rheumatoid arthritis, renal diseases and tumors, all of which are characterized by significant chronic inflammation [ 12 , 13 , 14 ]. It has been associated with the ability of NLRP3 inflammasome to sense and be activated by a plethora of DAMPs, including β-amyloid plaques, cholesterol and uric acid crystals, and oxidized low-density proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 inflammasome has been implicated in promoting the progression of several malignancies by influencing the intrinsic invasiveness of the tumor while also promoting the process of epithelial-mesenchymal transition (EMT) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Indeed, NLRP3 has been shown to be overexpressed by many cancers, while elevated levels of tumor NLRP3 expression have also been associated with an inferior clinical prognosis [ 15 , 21 , 22 , 23 ]. This is consistent with data showing NLRP3 amplification across several solid tumor types, implicating NLRP3 as a potential oncogene [ 24 ].…”
Section: Nlrp3 In Cancermentioning
confidence: 99%